Expected multi-utility representations - Tsogbadral Galaabaatar; Edi Karni (The Johns Hopkins University, Department of Economics, 2012)
This paper axiomatizes expected multi-utility representations of incomplete preferences under risk and under uncertainty. The von Neumann-Morgenstern expected utility model with incomplete preferences is revisited using a "constructive" approach, as opposed to earlier treatments that use convex analysis.
Keywords: 330; Incomplete preferences; Multi-utility representations